EKSISTENSI HUKUM ISLAM DI INDONESIA DALAM PEMBANGUNAN NASIONAL - Hendra Gunawan (Institut agama islam negeri Padangsidimpuan, 2018)
Islamic law brought by the prophet Muhammad, popularized by jargon “wama arsalnaka ila rahmatan lil'alamin” (not the message of Islam was revealed, but for the benefit of the entire universe) that govern the lives of Muslims in particular and mankind in general correspond to Islam derived its name from